Analisis Motivasi Dan Pengaruhnya Terhadap Prestasi Kerja Pegawai Pada Kecamatan Cendrana Kabupaten Maros - Muhtazib Muhtazib; Andi Bintang Balele (BADAN PENERBIT STIEPARI PRESS, 2022)
The research objective to be achieved is to determine the motivation factors and work performance of employees in Cendrana District, Maros Regency, South Sulawesi Province. The research method used is quantitative research methods. Taken together, all research variables, namely: providing incentives, giving awards, work environment, education & training and job promotions have a positive and significant influence on employee performance. Thus, this research hypothesis can be proven true or accepted. Partially, providing incentives in the form of rewards has the most dominant influence on employee performance. The large influence and contribution was due to an increase in job satisfaction, as a result of improved welfare for employees of Cendrana District, Maros Regency, South Sulawesi.